Design and Implementation of Training Mechanical Ventilator Set for Clinicians and Students - Guler, Hasan; Ata, Fikret (Elsevier Science Bv, 2013)
Mechanical ventilator is a widely used device generating a controlled a flow of gas into patient's lungs in anesthesia and intensive care units. The patients are usually connected with the ventilator through an endotracheal tube (ETT). Oxygen, which is the most important gas for keep human alive, is moved to the patient's lung by ventilators according to settings predetermined by clinicians. Clinicians have to determine the best treatment for patients because of the fact that ventilators generally work as open-loop controlled. Thus, a training mechanical ventilator set was designed and implemented to enhance the experiences of them. Besides, this set can be used in the medicine, veterinary and biomedical engineering studies' theoretical and experimental works, too. PLC, programmable logic controller, was used to control the system. It controls inspiration/expiration valves and evaluates pressure info received from pressure sensors. Inspiration/expiration time and operation mode can be easily changed on screen. Thanks to implemented training set, clinicians can make practice using of this ventilator set and students can increase their knowledge about respiratory system. The designed and implemented set is cheaper than ventilator used in intensive care units. (C) 2013 The Authors. Published by Elsevier Ltd.
2nd World Conference on Educational Technology Researches (WCETR) -- JUN 27-29, 2012 -- Near E Univ, Nicosia, CYPRUS
Keywords: Mechanical Ventilator; Respiration; PLC